Enhancing Elementary Students’ Communication and Collaboration Skills through Folklore-Based Role Playing in Indonesian Learning - Hafifa Lita; Banu Setyo Adi (Journal of Education and Teaching Learning, 2026)
Communication and collaboration skills are essential competencies in elementary school learning. This study examined the effect of a folklore-based role-playing learning model on fourth-grade students’ communication and collaboration skills in Indonesian language learning. The research used a quantitative quasi-experimental method with a non-equivalent control group pre-test–post-test design. The population consisted of fourth-grade students from four public elementary schools in Kadia and Kambu Districts. Samples were selected through purposive sampling, with SD Negeri 100 Kendari as the experimental and control school. Data were analyzed using Paired Sample T-test and MANOVA. The results of the study show that: 1) there is an influence of the Role Playing Folklore learning model in Indonesian language subjects on students' communication skills in elementary schools, evidenced by a significance value of 0.019 <0.05. 2) there is an influence of the Role Playing Folklore learning model in Indonesian language subjects on students' collaboration skills in elementary schools, evidenced by a significance value of 0.011 <0.05. 3) The results of the analysis using the Manova Pillai's Trace, Wilk Lambda, Hotelling's Trace, and Roy's Largest Root tables, show a significance of 0.000 <0.05, so it can be said that using the Role Playing Folklore learning model in Indonesian language subjects has an effect on students' communication and collaboration skills in elementary schools .